CFD AND EXPERIMENTAL ANALYSIS ON THERMAL PERFORMANCE OF EXHAUST SYSTEM OF A SPARK IGNITION ENGINE - Durat, Mesut; Parlak, Zekeriya; Kapsiz, Murat; Parlak, Adnan; Ficici, Ferit (TURKISH SOC THERMAL SCIENCES TECHNOLOGY, 2013)
Catalysts of a gasoline engine become active when the exhaust temperature exceeds 200 degrees C. Cold start HCs are extremely high until catalysts reach the light-off temperature. Determination of optimum place necessary time of the catalyst to reach this temperature is of vital importance. Interaction between exhaust gas and inner wall, along with the exhaust pipe needs to be well-understood. The interaction can be computed by numerical solutions based on fluid dynamics and heat transfer equations depending on time and location. In the study, three-dimensional transient CFD analysis has been performed for the whole exhaust pipe. The results of CFD analysis was in very good agreement with those of experimental data. Also, an optimal catalyst location was determined by the CFD analysis performed in transient regime. Heat transfer phenomena were also investigated analytically using different Nusselt number correlations given in the literature. Analytic results were compared with those of the experimental data. Each correlation gave reasonable results with different range of Reynolds number.
Keywords: Exhaust Pipe; Catalyst; Computational Fluid Dynamics; CFD; Heat Transfer Analysis; HEAT-TRANSFER; EMISSIONS; DESIGN; Thermodynamics; Engineering